Soil aggregates, carbon and nitrogen distribution, and water infiltration as influenced by mulching practices in a laterite mango (Mangifera indica L.) orchard - Yan, Chengming; An, Dongsheng; Zhao, Baoshan; Ma, Haiyang; Liu, Yanan; Kong, Ran; Su, Junbo (Journal of soils and sediments, 2023)
Purpose Mulching management is one of the most effective measures to alleviate soil erosion and improve soil quality in clean tillage orchards. However, the effects of mulching management patterns on carbon and nitrogen distribution have not been fully investigated, and water infiltration in the system is still unclear. This study aims to clarify the effects of mulching management on soil aggregates, carbon and nitrogen distribution, and water infiltration in subtropical clean tillage orchards in China. Methods In this study, we focused on a typical latosol mango orchard in China subject to subtropical monsoon climate conditions. Traditional bare soil cleaning tillage management was applied to the control area, and two treatments (i.e., Stylosanthes guianensis covering and horticultural ground fabric mulching) were set up. Soil aggregates and aggregate-associated carbon and nitrogen were investigated in three soil depths (0–15 cm, 15–30 cm, and 30–45 cm). The water content was monitored in 0–100 cm soil layer. Results Compared to clean tillage (CK), horticultural ground fabric mulching (GC) and Stylosanthes guianensis covering (SC) significantly improved the stability of soil aggregates and the proportion of > 0.25-mm water-stable aggregates in the three soil layers. And SC increased the SOC contents by 11.1% and 23.2% in the 0–15 cm and 15–30 cm soil layer while increased the TN contents by 8.3 and 24.6%, respectively. Moreover, it increased the SOC stock by 18.2% in the 15–30 cm soil layer. GC only increased 17.4% in SOC content in the 15–30 cm layer but no significant changes on SOC stocks, TN contents, and stocks in the three soil layers. However, GC is conducive to the water storage in the 0–100 cm soil layer and infiltration into the > 100 cm soil layer compared to SC. Conclusion In conclusion, covering Stylosanthes guianensis seems to have the best enhancing effect on soil quality in subtropical orchards but restriction the water into the > 100 cm soil layer. And small macroaggregates (0.25‒2 mm) favored the enhancement of the SOC and TN contents. The findings may be useful for clean tillage orchard management in subtropical China.